2018
DOI: 10.1186/s12870-018-1544-6
|View full text |Cite
|
Sign up to set email alerts
|

Canopy attachment position influences metabolism and peel constituency of European pear fruit

Abstract: BackgroundInconsistent pear fruit ripening resulting from variable harvest maturity within tree canopies can contribute to postharvest losses through senescence and spoilage that would otherwise be effectively managed using crop protectant and storage regimes. Because those inconsistencies are likely based on metabolic differences, non-targeted metabolic profiling peel of ‘d’Anjou’ pears harvested from the external or internal canopy was used to determine the breadth of difference and link metabolites with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 88 publications
7
15
0
4
Order By: Relevance
“…p -Coumaroyl-triterpenoids constituted approximately 1% of the wax compounds at maturity ( Table 2 ). Similar hydroxycinnamate esters of triterpenoids have been detected in apple ( McGhie et al , 2012 ) and pear peels ( Serra et al , 2018 ). To the best of our knowledge, this is the first report of the presence of these compounds in the cuticular waxes of rosaceous fruits.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…p -Coumaroyl-triterpenoids constituted approximately 1% of the wax compounds at maturity ( Table 2 ). Similar hydroxycinnamate esters of triterpenoids have been detected in apple ( McGhie et al , 2012 ) and pear peels ( Serra et al , 2018 ). To the best of our knowledge, this is the first report of the presence of these compounds in the cuticular waxes of rosaceous fruits.…”
Section: Discussionsupporting
confidence: 62%
“… Lv et al (2016) showed that the contents of oleanolic and ursolic acids on the shaded side of apples were higher than those on the sun-exposed side. In pear peels, the levels of the different triterpene groups showed significant and contrasting variations depending on the fruit position in the canopy ( Serra et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, low predicted dry matter fruits were generally evaluated less favourably in Orchard 2 than in Orchard 1 among most sensory attributes, and high dry matter fruits were evaluated more favourably in Orchard 2 than in Orchard 1. This would seem to suggest the quality variation introduced from the older, larger open‐canopy trees that characterise Orchard 2 (Serra et al ., ) is detectible by the consumer, particularly at the margins of what constitutes market‐acceptable fruit. As well, fruits grown in 2016 were generally more liked across numerous attributes than fruits grown in 2017.…”
Section: Resultsmentioning
confidence: 62%
“…Characterizing fruit metabolic shifts in response to preharvest factors is key to fruit quality improvement, as several of these compounds contribute to organoleptic characteristics that correlate with consumer preference. Many studies have reported effects of various preharvest and orchard factors on tree fruit quality (Minas et al, 2018, Musacchi andSerra, 2018). However, despite the enormous advances in "omics" sciences, few experiments have addressed the influence of these preharvest factors on fruit quality at the metabolic level (Monti et al, 2016;Serra et al, 2018;Michailidis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported effects of various preharvest and orchard factors on tree fruit quality (Minas et al, 2018, Musacchi andSerra, 2018). However, despite the enormous advances in "omics" sciences, few experiments have addressed the influence of these preharvest factors on fruit quality at the metabolic level (Monti et al, 2016;Serra et al, 2018;Michailidis et al, 2020). Furthermore, it is important to highlight that these previous studies did not control for equal maturity when analyzing fruit coming from various preharvest conditions.…”
Section: Introductionmentioning
confidence: 99%